Penerapan Kolaboratif E-Government Pada Pelayanan Kepegawaian Badan Kepegawaian Daerah Provinsi Sumatera Barat - Debby Putri Pratama; Roni Ekha Putera; Hendri Koeswara (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2023)
Collaborative E-Government not only changes the way government organizations carry out their duties but also changes the way the government interacts with its citizens in public services. This research aims to analyze and obtain a model regarding the implementation of collaborative E-Government at the Regional Civil Service Agency of West Sumatra Province in providing personnel services as proof that this collaborative E-Government is a solution to the never-improving quality of public services. This research uses a qualitative research method with a descriptive approach. Data collection techniques were carried out through interviews and documentation, where the informants in this research were selected purposively. The research results show that there is a dominance of fulfilling elements in the implementation of collaborative E-government, which has implications for improving personnel services in Regional Government. The only obstacles to collaboration are the network structure, governance, and access to resource elements. Thus, collaboration between actors in personnel services has become a solution to poor personnel service practices in local governments and has contributed to the development of literature on personnel service practice issues.